2020
DOI: 10.3390/ijerph17051680
|View full text |Cite
|
Sign up to set email alerts
|

Does Better Health-Related Knowledge Predict Favorable Health Behavior in Adolescents?

Abstract: The importance of puberty on later health status and behavior is indisputable, which also means that it is worth making intervention efforts during this period of life. However, whether better health-related knowledge is correlated with favorable health behavior in adolescents is an important, still unanswered question. Our objective was to examine this relationship. The participants were ninth-grade secondary school students. Data were collected using anonymous, self-administered questionnaires. The knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 27 publications
1
35
3
1
Order By: Relevance
“…Hence, there existed a gap between declarative knowledge and behaviors. Several studies have confirmed that healthy eating knowledge is a significant predictor of both future knowledge and behavior [ 30 , 31 , 32 , 33 ]; however, knowledge alone is not sufficient to change the food behaviors of consumers, as such behaviors can also be influenced by personal, intra-individual, and environmental factors, including motivations [ 34 , 35 , 36 ]. The results of our cluster analysis underline that one such factor could be “Emotional” motivations; at least, for Emotional eating consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there existed a gap between declarative knowledge and behaviors. Several studies have confirmed that healthy eating knowledge is a significant predictor of both future knowledge and behavior [ 30 , 31 , 32 , 33 ]; however, knowledge alone is not sufficient to change the food behaviors of consumers, as such behaviors can also be influenced by personal, intra-individual, and environmental factors, including motivations [ 34 , 35 , 36 ]. The results of our cluster analysis underline that one such factor could be “Emotional” motivations; at least, for Emotional eating consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Students are young adults whose first university years represent a period of vulnerability, in which the prevalence of symptoms such as depression and anxiety are steadily growing [ 6 ]. The early university years are an important stage for the acquisition of behavioral habits [ 7 , 8 , 9 , 10 ], as many students leave their family homes to start their university studies and to live independently [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with many previous studies that found that taste and cost-rather than knowledge-are the main food choice drivers for adolescents. 51,53,56,[63][64][65][66][67][68] Meanwhile, limited break time and an abundance of attractive and cheap unhealthy foods compared to healthy foods create barriers to healthy eating at school. [69][70][71][72] Thus, our findings support previous research that identified the importance of removing unhealthy options from school canteens.…”
mentioning
confidence: 99%